Force balance at the magnetopause determined with MMS: Application to flux transfer events. Issue 23 (9th December 2016) - Zhao, C.; Russell, C. T.; Strangeway, R. J.; Petrinec, S. M.; Paterson, W. R.; Zhou, M.; Anderson, B. J.; Baumjohann, W.; Bromund, K. R.; Chutter, M.; Fischer, D.; Le, G.; et al.
Abstract: The Magnetospheric Multiscale mission (MMS) consists of four identical spacecraft forming a closely separated (≤10 km) and nearly regular tetrahedron. This configuration enables the decoupling of spatial and temporal variations and allows the calculation of the spatial gradients of plasma and electromagnetic field quantities. We make full use of the well cross‐calibrated MMS magnetometers and fast plasma instruments measurements to calculate both the magnetic and plasma forces in flux transfer events (FTEs) and evaluate the relative contributions of different forces to the magnetopause momentum variation. This analysis demonstrates that some but not all FTEs, consistent with previous studies, are indeed force‐free structures in which the magnetic pressure force balances the magnetic curvature force. Furthermore, we contrast these events with FTE events that have non‐force‐free signatures. Key Points: Demonstrates flux transfer events are not necessarily force free Finds that in non‐force‐free FTEs, the magnetic force is balanced by the ion pressure gradient force; the electron pressure can be ignored Minimum variance analysis on the magnetic pressure gradient force gives the best estimate of the axial direction of flux ropes